"Asociaciones de moluscos de las terrazas marinas cuaternarias de Río Negro y Chubut, Argentina" (Ameghiniana, 2014)
"Multivariate analysis (cluster and principal component analysis) were used to correlate a total of 33 deposits from 10 Quaternary marine terraces in central and northern Patagonia. Fifty four mollusc taxa (30 species of gastropods and 24 of bivalves) were included in this study. The results support the stratigraphic scheme proposed by Feruglio in 1950.Three biofacies were defined, with subdivisions in two of them. Association la"" which includes extinct species in the adjacent coast at the same latitude, belongs to deposits of level B2 (Level 5 in Feruglios arrangement). Association lb includes intertidal and rocky-bottom molluscs, allliving in the adjacent sea, and defines biofacies B1 (Level6 of Feruglio). Biofacies C includes Association 2, of Magellanic, hard-bottom molluscs that live at the same latitude today. The latter biofacies is partially equivalent to Level 4 of Feruglio's scheme. In agreement with Feruglio's conclusions, four terraces are of Quaternary age (Levels 3-6). The earliest Quaternary terrace is the third one, represented in very few deposits with a minimum height of 40 m a.s.l. to a maximum of 95m a.s.l. All species in this deposit are extant, except one unnamed species of Ostrea. The suggested temperature during the deposition of this level is warmer than the present temperature at the same latitude. The southern limits of the present ranges of the recorded species lie farther north of the Valdés Peninsula. According to Feruglio, this deposit represents an interglacial period, probably the penultimate. Level 4 was dated by different methods in several deposits with absolute ages around 116.000years BP and more than 350.000 years BP.Thefossils are cemented, and belong to warm-water species, with some cold-water survivors from the south. Level 5 is considered the final phase of the last glacial periodo It was dated between 110.000to 80.000 years BP.Most of the species from this deposit are found in cold waters of the Magellanic province today. Different dating methods confirm that Level6 includes only Holocene deposits. The fossils are not consolidated, and they represent species that live at the same latitude today. The highest levels of Quaternary marine terraces are older than the last interglacial, probably corresponding to the penultimate interglacial lapse. The intermedia te levels represent the last interglacial, whereas the lowermost levels are Holocene in age."